2022
DOI: 10.30541/v48i4iipp.715-738
|View full text |Cite
|
Sign up to set email alerts
|

Do Foreign Inflows Benefit Pakistani Poor?

Abstract: Foreign Inflow plays an important role in country’s development. The importance of foreign inflows is not limited to developing countries; developed and emerging economies also attract foreign inflows to supplement their resources to sustain growth. The importance of foreign inflow in Pakistan is very well acknowledged and documented, however the affect of these inflows on poor people of Pakistan remains unanswered. This paper is an attempt to fill this gap by studying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 40 publications
6
31
2
Order By: Relevance
“…Similarly, few studies conclude that there is a negative impact of FDI on poverty reduction (e.g. Ali et al, 2010;Huang et al, 2010). The findings of these studies present in Table 2 that inflows of FDI lead to a rise in the level of poverty, opposite to theoretical predictions (Table 2).…”
Section: Empirical Literature Reviewmentioning
confidence: 84%
See 2 more Smart Citations
“…Similarly, few studies conclude that there is a negative impact of FDI on poverty reduction (e.g. Ali et al, 2010;Huang et al, 2010). The findings of these studies present in Table 2 that inflows of FDI lead to a rise in the level of poverty, opposite to theoretical predictions (Table 2).…”
Section: Empirical Literature Reviewmentioning
confidence: 84%
“…The Warr (2000), Hsiao and Hsiao (2006), Dollar et al (2013) and Feeny, Iamsiraroj, and McGillivray (2014) explored the nexus FDI and poverty through economic growth channel, whereas, limited research has been done on the direct relationship between FDI and poverty reduction. Moreover, several past studies revealed a strong and positive impact of FDI on poverty reduction, but few studies such as Huang et al (2010) and Ali et al (2010) found that FDI influences inversely on poverty reduction. These studies concluded that FDI increasing poverty in these countries and these results are contractions to theoretical hypotheses.…”
Section: Empirical Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…However, apart from studies that have found a positive impact of FDI on poverty reduction, there are also a few studies that have found a negative impact of FDI on poverty reduction. These studies include Huang et al (2010) and Ali and Nishat (2010). Huang et al (2010) examined the impact of FDI on poverty in 12 countries from East and Latin America between 1970 and 2005.…”
Section: A Review Of the Empirical Literature On The Impact Of Fdi Onmentioning
confidence: 99%
“…Using unbalanced panel data, they found inward FDI to have a negative impact on poverty reduction. Ali and Nishat (2010) used time series data on Pakistan from 1973 to 2008 to investigate the relationship between FDI and poverty. Employing Autoregressive Distributed Lag (ARDL) and using the poverty headcount as a proxy of poverty, they found FDI inflows to have a negative impact on poverty reduction in Pakistan in both the short and long run.…”
Section: A Review Of the Empirical Literature On The Impact Of Fdi Onmentioning
confidence: 99%